The Digital Literacy and Social Media Content-Making Training Program for SMEs and Housewives in the Hepi Bandung Community - Moh Faidol Juddi; Agus Aprianti (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
New media usage, particularly network-based media using mobile platforms, has become a big issue in the community. Various issues arise related to the presence of information technology and its intersection with daily activities and other social environments. There has yet to be a corresponding growth in people's awareness of online ethics in Indonesia with the surge in internet use. Housewives, in particular, frequently do sharenting and oversharing on the internet. Awareness of the risks associated with online flaming and cyberbullying is also essential. Thus, it is crucial to successfully promote digital literacy among housewives in the HEPI Bandung community to raise awareness of online ethics. It is also critical to comprehend the technical facets of branding for both personal and professional purposes. This program seeks to educate participants about digital literacy and digital content creation workshops to assist them in avoiding adverse outcomes down the road, particularly for housewives. This activity had two phases: material distribution (including a workshop) and sharing sessions. Increasing the participants' knowledge is the purpose of the content delivery. The two-way sharing session aims to broaden participants' knowledge and answer their problems appropriately. Evaluate the activities by sending out feedback surveys. The evaluation's conclusions show how successfully literacy-related activities have addressed participants' needs. Increasing digital literacy is a positive thing, mainly as we use digital media to become a better-informed society. Furthermore, the participants hope that such literacy exercises continue in parallel to evaluate and improve the understanding that has been established collectively.